Dynamic analysis of ribosome by a movie made from many three-dimensional electron-microscopy density maps - Atsushi Matsumoto (Biophysics and Physicobiology, 2019)
The atomic models of the 70S ribosome including the bound molecules were built from many 3D-EM density maps. The positions and conformations of the bound molecules were determined by fitting them to the regions in the density maps which remained after fitting the 70S ribosome. Then, using these atomic models, a movie for the elongation cycle was made. For determining the sequential order in which the models appeared in the movie, the knowledge about the bound molecules and the ratchet angles were used. The movie revealed several interesting points which were not apparent from each density map, suggesting the usefulness of a movie made from many 3D-EM density maps.